SOSIALISASI DESIGN MIX FORMULA ASPAL KARET ALAM PADAT(AKAP-PG76) DAN JOB MIX FORMULA di P.T. BINTANG SELATAN AGUNG - Sumiati; Mahmuda; Rizki Prasetya Person (Politeknik Negeri Sriwijaya, 2024)
Abstract Solid rubber natural asphalt (AKAP-76) is asphalt modified using vulcanized natural rubber polymer SIR 20, produced by PT. Modified Bitumen, is a new variant whose use has not been tested. Kerdosma Research has carried out a Mix Design Formula to determine the superiority of solid natural rubber asphalt (AKAP-PG76) in asphalt concrete mixtures (AC-WC) using aggregates originating from Quarry P.T. Bintang Selatan Agung. PT Bintang Selatan Agung is a company that operates in the field of civil construction of roads and runways, and has its own Asphalt Mixing Plant (AMP) to prepare road pavement mixtures, which currently do not use solid natural rubber asphalt (AKAP-76). Therefore, on this occasion there will be socialization of Mix Design Formula using solid natural rubber asphalt (AKAP-76) and sharing of Job mix formula for Asphalt Mixing Plant at P.T. Bintang Selatan Agung. The conclusion obtained is that: Formula Design Mix must be carried out because it is a guideline for making Job mix designs, especially in terms of aggregate composition and optimum asphalt content in order to obtain an asphalt concrete mixture that meets the Marshall parameter values ​​based on specifications. Keywords: design mix formula, job mix formula, AKAP-PG76